Blogs and news sources coverage in altmetrics data providers: a comparative analysis by country, language, and subject - Ortega, José Luis (Scientometrics, 2020)
The main objective of this study is a detailed analysis of the coverage of blogs and news by three of the most important altmetrics data providers (Altmetric.com, PlumX, and Crossref Event Data). Concretely, the study looks for differences in blogs and news coverage, according to three criteria: country, language, and subject, with a view to detecting biases that influence altmetrics impact. More than 100,000 random publications from Crossref were searched in all three providers. The link, title, and source of the events that mention each document were retrieved. Each source was classified according to the three criteria. Results show that over 65% of blogs and news come from English-speaking countries and over 75% are written in English. In terms of subject matter, General-interest news outlets (> 50% in PlumX and Altmetric.com) and Social Sciences and Humanities blogs (> 20%) prevail. Altmetric.com is the most geographically and linguistically heterogeneous service, with the best coverage of blogs; PlumX collects more news media, especially local-interest newspapers from the United States; and Crossref Event Data is the platform that brings together most English-speaking sources.